Identification of Salmonella sp. bacteria Using ISO 6579-1:2017 Method for Frozen Salmon (Salmo salar) Products - Wulan Agus Utami, Annisa; Sari, Deva Dewiyana; Nirmalasari; Roza Sani Aidah; Rusdi; Sari Utami Hidayati (Journal Of Biology Education Research (JBER), 2025)
Salmon is a type of marine fish from the Salmonidae family that lives in the Atlantic Ocean, both on the northern coast of America and Europe, as well as the Pacific Ocean. Salmonella sp. being one of the pathogenic bacteria that causes human disease through food and drink. Contamination can occur at any stage of the food production, distribution and consumption chain. Tests carried out to identify Salmonella bacterial contamination use the ISO 6579-1:2017 test method. This test consists of pre-enrichment, enrichment, plating out and biochemical tests. Identification of Salmonella sp bacteria on frozen salmon products at the BUSKIPM Quality Microbiology Laboratory using the ISO 6579-1:2017 standard test method showing negative test results for Salmonella sp. The reading of the results of the confirmation test carried out did not meet the specific requirements for Salmonella sp. bacteria.